2018
DOI: 10.1111/aos.13661
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise and glaucoma: a review on the roles of physical exercise on intraocular pressure control, ocular blood flow regulation, neuroprotection and glaucoma‐related mental health

Abstract: The benefits of physical exercise on health and well-being have been studied in a wide range of systemic and ocular diseases, including glaucoma, a progressive optic neuropathy characterized by accelerated apoptosis of retinal ganglion cells (RGCs). Elevated intraocular pressure (IOP) and insufficient ocular perfusion have been postulated to be the two main theories in glaucoma development and progression. The effects of exercise in these two aspects have been demonstrated by numerous researches. A review in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 180 publications
(348 reference statements)
3
56
1
6
Order By: Relevance
“…The IOP increases reported in these posture and nocturnal variation (or physical exercise (Zhu et al. ) studies, however, are strongly exceeded by the external pressure‐induced increase in estimated IOPs found in our study, which was also found in 9 volunteers (Korenfeld & Dueker ,b). Additionally, we showed that wearing protective eye gear prevents this large external pressure‐induced IOP increase, a finding confirmed by a similar effect described wearing a customized protective mask (Flatau et al.…”
Section: Discussioncontrasting
confidence: 56%
“…The IOP increases reported in these posture and nocturnal variation (or physical exercise (Zhu et al. ) studies, however, are strongly exceeded by the external pressure‐induced increase in estimated IOPs found in our study, which was also found in 9 volunteers (Korenfeld & Dueker ,b). Additionally, we showed that wearing protective eye gear prevents this large external pressure‐induced IOP increase, a finding confirmed by a similar effect described wearing a customized protective mask (Flatau et al.…”
Section: Discussioncontrasting
confidence: 56%
“…La PIO alta es un factor de riesgo para la salud visual, especialmente porque puede ser la causante de presentar glaucoma, uno de los principales causantes de la ceguera a nivel mundial (Aspinall et al, 2008;Era et al, 2009;Leighton, 1972;Zhu et al, 2018). Estudios que datan desde los años setentas muestran los posibles efectos de la actividad física en los parámetros de la PIO (Leighton, 1972), estos pioneros brindaron las bases para ir esclareciendo conocimiento, así como el involucramiento de variables que podrían tener un efecto sobre la PIO (Dane et al, 2006).…”
Section: Resultsunclassified
“…Estos valores se pueden obtener por medio de una tonometría, método utilizado con mucha frecuencia para conocer los niveles de presión intraocular. Una PIO elevada representa un factor de riesgo modificable que se puede y debe controlar, para prevenir el desarrollo o progreso del glaucoma (Aspinall et al, 2008;Era, Pärssinen, Kallinen, & Suominen, 2009;Leighton, 1972;Zhu et al, 2018) .…”
Section: Antecedentes Teóricosunclassified
See 1 more Smart Citation
“…Sowohl bei Gesunden als auch bei Glaukompatienten kann hierdurch zumindest kurzzeitig der IOD gesenkt werden. Dieser Effekt ist additiv zu antiglaukomatösen Augentropfen und ist mehr von der Intensität als von der Dauer der Belastung abhängig [14]. Ein weiterer Effekt von Ausdauersport kann eine Verbesserung des okulären Perfusionsdrucks durch eine Kreislaufstabilisierung sein, was insbesondere beim Normaldruckglaukom wichtig ist [15].…”
Section: Körperliche Bewegungunclassified